Experimental Study of Grippferon Antiviral Activity Against Mexican Pandemic Influenza Virus A/H1N1/2009 in vitro - S. YA. Loginova; S. V. Borisevich; V. N. Shchukina; G. V. Borisevich; V. P. Bondarev; V. A. Shevtsov (Антибиотики и Химиотерапия)
Analysis of the efficacy of Grippferon vs. the reference drugs Realdiron and Reaferon-EC against the influenza virus A(H1N1)/2009 in susceptible static cell cultures showed that in the concentrations tested it was efficient in inhibition of the virus cytopathic activity and generation of specific hemagglutinin.